Performance of the Asset Sector at the Aceh Barat Daya Regency Financial Management Agency in Managing Regional Property - Novita, Puja (Institut Bisnis dan Informatika Kesatuan, 2024)
The Asset Division of the Regional BPK of Aceh Barat Daya Regency has done a good job in managing 's Regional Property, but its human resources are not sufficient to handle the existing workload. This is due to the very limited Regional Budget (APBD), which means it is still lacking. The purpose of this study was to determine the efficiency of the asset sector in managing Regional Property at the Regional Financial Management Agency of Aceh Barat Daya Regency. According to Bodgan and Taylor, qualitative research is a method for collecting descriptive information from witnesses or interviewees through written or oral statements, this research uses case study methodology. The Aceh Barat Daya District Financial Management Agency (BPKK) was the focus of this investigation. The data used in this study were obtained from interviews with the Head of Assets of BPKK Aceh Barat Daya and the position, organizational structure, duties, functions, and work procedures of BPKK Aceh Barat Daya as outlined in Perbup No. 7/2021. Based on the results of the research, the BPKK Asset Division has complied with the rules and regulations relating to the management of regional property and state property in Aceh Barat Daya, as stipulated in PP No. 27 of 2014 and Permendagri No. 19 of 2016.